USABILITY TESTING OF THE IFS PRO ANDROID MOBILE APPLICATION FOR CRYPTOCURRENCY TRADING SIGNAL FORECASTING USING THE CONCURRENT THINK-ALOUD (CTA) TECHNIQUE AND PERFORMANCE MEASUREMENT - I Gede Etika Ari Wibawa (RADJA PUBLIKA, 2026)
The IFS Pro android application is a decision support application for cryptocurrency traders determining a buy or sell position when trading. Since its inception until now, IFS Pro has never evaluated the user and system performance aspects, so it is not known whether the system has run well or not. Based on these problems, researchers conducted an evaluation using usability testing with CTA techniques and Performance Measurement. The results of the analysis for the effectiveness of the IFS Pro android application are said to be effective because there are no errors (0%) made by respondents from the Performance Measurement data. Then the results of the efficiency analysis have been efficient because there is no significant time difference from the Mann Whitney U-test data. The results of the analysis of user satisfaction based on the features of the IFS Pro android application have a fairly satisfying category with an average value of 61 (C) obtained from the CTA usability data with the SUS (System Usability Scale) questionnaire. Because IFS Pro user satisfaction is still in the quite satisfied category, the researchers assess the need for improvement recommendations, including adding features and display adjustments. Suggestions for the future, IFS Pro periodically carries out usability testing analysis on the IFS Pro android application so that the quality of the IFS Pro user satisfaction category is getting better.